A Comprehensive Analysis of Global Digital Payment Systems: A Systematic Literature Review (2019–2025) (International Journal of Economics and Management Research, 2026)
The development of information and communication technology (ICT) has significantly influenced the global financial sector. One of the most important innovations is the digital payment system, which has transformed the way people perform financial transactions—making them faster, safer, and more efficient. This study aims to identify the trends, theories, methods, and research gaps related to digital payment systems through the Systematic Literature Review (SLR) approach.Data were collected from ten international scientific articles indexed in Scopus and ScienceDirect between 2015–2025. The findings reveal that the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) are the most dominant theories explaining user adoption behavior. The main influencing factors include trust, security, ease of use, and perceived risk.This study highlights a paradigm shift from technical aspects toward behavioral and regulatory perspectives. Future research should focus on cross-platform integration, blockchain-based security, and the development of digital financial literacy policies.